Diagenesis of sulfur, iron and phosphorus in sediments of an urban bay impacted by multiple anthropogenic perturbations. (September 2019) - Ma, Wei-Wei; Zhu, Mao-Xu; Yang, Gui-Peng; Li, Wen-Jun; Meng, Tao; Li, Tie
Abstract: Solid-phase speciation and porewater chemistry measured by the diffusive gradients in thin films (DGT) technique were used to understand the diagenesis of sulfur (S), iron (Fe), and phosphorus (P) in sediments of Jiaozhou Bay (China), which has been impacted by multiple anthropogenic perturbations. Despite water eutrophication, sediments of the bay are low in organic carbon and sulfide, but high in unsulfidized Fe(II). Dissimilatory iron reduction (DIR) prevails in sediments of the bay, and there is no evidence for responses of S and Fe diagenesis to the water eutrophication, which is largely attributable to unique depositional and diagenetic regimes in association with multiple anthropogenic perturbations. Good coupling of porewater Fe 2+ and P in the porewaters suggests that P mobilization is driven mainly by DIR. Low Fe 2+ /P ratios in porewaters imply that oxidative regeneration of Fe oxides within the upper sediments is incapable of efficiently scavenging upward diffusing P. Highlights: Dissimilatory iron (Fe) reduction prevails in sediment of eutrophic Jiaozhou bay. Diagenesis of sulfur (S) and Fe in the sediment is decoupled to water eutrophication. Multiple anthropogenic perturbations have no net impacts on Fe and S diagenesis. Phosphorus mobilization is mainly driven by reductive dissolution of Fe oxides.